Pose estimation project - Rosenhahn, B. (2006)
The research project deals with the 2D-3D pose estimation problem. A modified version of this page can also be found at the official 2D-3D pose estimation project page from the cognitive systems group at the University of Kiel. Pose estimation itself means to estimate the relative position and orientation of a 3D object with respect to a reference camera system.